2010
DOI: 10.1186/1475-925x-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Towards the creation of decellularized organ constructs using irreversible electroporation and active mechanical perfusion

Abstract: BackgroundDespite advances in transplant surgery and general medicine, the number of patients awaiting transplant organs continues to grow, while the supply of organs does not. This work outlines a method of organ decellularization using non-thermal irreversible electroporation (N-TIRE) which, in combination with reseeding, may help supplement the supply of organs for transplant.MethodsIn our study, brief but intense electric pulses were applied to porcine livers while under active low temperature cardio-emula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 54 publications
2
65
0
Order By: Relevance
“…The lethal thresholds for U87 brain cancer cells found in this study were 463 V/cm and 505 V/cm in 3D and 2D models, respectively, when 100 × 100 μs monopolar IRE pulses were delivered. Previous studies found lethal thresholds in liver tissue between 300 and 640 V/cm using similar IRE protocols363738, indicating that both the 2D and 3D culture models recapitulate effects seen in mammalian tissue. Fourteen of sixteen protocols conducted in 2D and 3D conditions showed no statistically significant difference in lethal threshold indicating that the 3D model has a limited effect on the lethal threshold and cells cultured in a 2D monolayer are a relatively effective model for studying H-FIRE.…”
Section: Discussionmentioning
confidence: 72%
“…The lethal thresholds for U87 brain cancer cells found in this study were 463 V/cm and 505 V/cm in 3D and 2D models, respectively, when 100 × 100 μs monopolar IRE pulses were delivered. Previous studies found lethal thresholds in liver tissue between 300 and 640 V/cm using similar IRE protocols363738, indicating that both the 2D and 3D culture models recapitulate effects seen in mammalian tissue. Fourteen of sixteen protocols conducted in 2D and 3D conditions showed no statistically significant difference in lethal threshold indicating that the 3D model has a limited effect on the lethal threshold and cells cultured in a 2D monolayer are a relatively effective model for studying H-FIRE.…”
Section: Discussionmentioning
confidence: 72%
“…However, one recent study has investigated the in vitro use of NTIRE combined with vascular perfusion to decellularize porcine liver. The results showed that perfusion with lactated ringer's solution facilitated removal of cellular debris resulting from electroporation, but also showed the limited effective geometric distribution of this approach [96]. The amount of cellular remnants retained within the tissue remains to be determined.…”
Section: Decellularization Agentsmentioning
confidence: 99%
“…In translational studies, large animals such as pigs and sheep are preferred [25,26,27,28,29,30,31,32]. The use of pigs as organ donors is discussed controversially because of the immunological barrier due to the expression of galactose-1,3-alpha-galactose in porcine organs which may lead to hyperacute rejection of the repopulated organ.…”
Section: Source Of Organs For Liver Engineeringmentioning
confidence: 99%
“…Other approaches concerning the optimization of the decellularization process were also tested such as the combination of electroporation with simultaneous perfusion [32]. The cryochemical method calls for freezing the freshly explanted liver in distilled water up to -80°C on the 1st day and slowly thawing on the 2nd day prior to starting perfusion.…”
Section: The Decellularization Processmentioning
confidence: 99%